Translating Curriculum Reform into Classroom Practice: A Qualitative Evaluation of the Merdeka Curriculum in English Language Teaching Using the CIPP Framework. - A. Zainuddin, Andi Husni; Sahraini; Thayyib, Magfirah (CV. DYOQU PUBLISHING MANAGEMENT, 2026)
Background: Curriculum reform has become an important strategy for improving educational quality and promoting student-centered learning in many education systems. In Indonesia, the Merdeka Curriculum was introduced to provide greater flexibility in teaching, encourage learner autonomy, and strengthen twenty-first-century competencies such as collaboration, communication, and critical thinking. However, translating curriculum policy into effective classroom practice remains challenging, particularly in English language teaching where pedagogical approaches, assessment practices, and learning resources must adjust to new instructional orientations. Aims: This study aims to evaluate how the Merdeka Curriculum is implemented in English language classrooms using the Context, Input, Process, and Product (CIPP) evaluation framework. Method: The research employed a qualitative design. Data were collected through semi-structured interviews with English teachers, classroom observations, and analysis of instructional documents related to curriculum implementation. Participants were selected purposively based on their involvement in applying the Merdeka Curriculum. The data were analyzed thematically according to the four dimensions of the CIPP model. Result: The findings indicate that the Merdeka Curriculum aligns conceptually with national education policies and institutional goals. Nevertheless, contextual adaptation remains limited, teacher training often emphasizes policy understanding rather than pedagogical application, and unequal digital resources influence instructional effectiveness. Classroom observations also reveal that teacher-centered practices still partially persist. Conclusion: The study concludes that successful curriculum reform requires sustained teacher professional development that prioritizes practical pedagogical transformation. Stronger institutional support, contextual adaptation, and equitable learning resources are essential to ensure that the principles of the Merdeka Curriculum can be translated into meaningful and student-centered classroom practices.